Impact of the lower energy threshold on the NEMA NU2-2001 count-rate performance of a LSO based PET-CT scanner - Eckardt, J.; Herzog, H.; Schäfers, K. P.; Käpplinger, S.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2008)
The aim of this study was to investigate the impact of the lower energy threshold (LET) on the NEMA NU2–2001 count-rate performance of a LSO-based PET scanner (Siemens PET-CT Biograph Sensation 16). The quantitative measurements were focused on three different aspects: noise equivalent count rate (NEC), scatter fraction, and absolute sensitivity. Methods: According to the NEMA-NU2–2001 protocol count-rate-performance (NEC-2R, scatter fraction) and sensitivity were evaluated performing serial measurements at LETs of 350, 375, 400, 410, 420, 430, 440, and 450 keV (the upper energy threshold was fixed to 650 keV). NEMA protocols were adapted to account for the intrinsic radioactivity of 176Lu in the LSO crystals. Results: Up to a radioactivity concentration of 8 kBq/ml the highest NECrates were obtained at an LET of 410 keV, between 8 and 20 kBq/ml at an LET of 420 keV and above 20 kBq/ml at an LET of 430 keV. The overall NEC maximum was 67 kcps at 430 keV (at 28 kBq/ml). The minimum scatter fraction was measured at a radioactivity concentration of ~ 0.5 kBq/ml. The scatter fraction decreased continuously from 45% at an energy threshold of 350 keV to 24% at 450 keV. The maximum sensitivity of 5.8 kcps/MBq, was obtained at an LET of 350 keV and the minimum sensitivity of 4.2 kcps/MBq at an LET of 450 keV. At the LET with the maximum NEC-rate (430 keV) the sensitivity was 4.8 kcps/MBq. Conclusion: The optimal count-rate performance of the LSO-based PET system was found at LETs between 410 keV and 430 keV depending on the actual radioactivity concentration placed in the scanner. A global maximum in NEC count rate was obtained at an LET of 430 keV.
Keywords: Instrumentation; performance; PET/CT; NEMA; LSO